Effect of removal of organic material on stable isotope ratios in skeletal carbonate from taxonomic groups with complex mineralogies. (16th August 2020) - Key, Marcus M.; Smith, Abigail M.; Phillips, Niomi J.; Forrester, Jeffrey S.
Abstract : Rationale: Stable oxygen and carbon isotope ratios are one of the most accurate ways of determining environmental changes in the past, which are used to predict future environmental change. Biogenic carbonates from marine organisms are the most common source of samples for stable isotope analysis. Before they are analyzed by mass spectrometry, any organic material is traditionally removed by one of three common pretreatment methods: roasting, bleaching, or with hydrogen peroxide at various strengths and durations. Methods: This study compares δ 18 O and δ 13 C values in a control with no pretreatment with those from five different pretreatment methods using conventional acid digestion mass spectrometry. The objectives are to: assess the impact of the most common pretreatment methods on δ 18 O and δ 13 C values from (1) taxonomically underrepresented groups in previous studies, and (2) those that precipitate a wide range of biomineralogies, in the debate of whether to pretreat or not to pretreat. We analyzed the following biomineralogically complex temperate marine organisms from southern New Zealand: four species of bryozoans, four species of molluscs, two species of arthropods, and one species each of annelid, red alga, brachiopod, and echinoderm (test plates and spines treated separately). These species precipitate aragonite, High‐, Intermediate‐, and/or Low‐Mg calcite (LMC) in their skeletons. We used linear mixed statistical models to compare the effects of the pretreatments and mineralogical composition on their δ 18 O and δ 13 C values. Results: Roasting was the most effective pretreatment for the removal of organic matter and light H2 O2 the least, but the former had corresponding impacts on isotope ratios. δ 18 O values were not directly affected by wt% MgCO3, but they were significantly affected by the interaction of roasting and wt% MgCO3 . This same negative effect of roasting on species with higher wt% MgCO3 occurred in δ 13 C values, but it was much more pronounced in δ 18 O values. Both H2 O2 pretreatments significantly and negatively affected δ 18 O values at higher wt% MgCO3 . Neither bleaching pretreatment significantly affected δ 18 O values. δ 13 C values were most negatively affected in skeletons with high wt% MgCO3 . There was also a strong negative roasting effect and more so at higher wt% MgCO3 . Bleaching and H2 O2 did not significantly affect δ 13 C values. Conclusions: Based on these results, and when using skeletal carbonate of complex mineralogies, we recommend considering the abandonment of pretreatment of biogenic carbonate for stable isotope analysis due to confounded results from previous studies, difficulties with preparation, and/or the absence of significant effects of organic material on isotope ratios. If pretreatment is necessary, avoid roasting especially at higher temperatures and durations, use minimal bleaching, and in general avoid using High‐Mg calcite species in O and C stable isotope studies. If bleaching is used, clearly indicate the concentration and duration of exposure.